Notes mozabites - Schacht, Joseph (Al-Andalus, 1957)
On Ibāḍī mosques in Ouargla, Mīzāb and at Jerba (with plans and photographs), on Ibāḍī cemeteries in Mīzāb, on style in Ibāḍī architecture, and finally some observations on “modernism and the movement of sheikh Ibr. Bayyūḍ” and on education in Mīzāb.
Keywords: Architecture – Mzab; Ghuraba; mosquée al- (Houmt Souk; Djerba); Jami al-Kabir; mosquée al- (Hachene; Djerba); Monuments – Djerba; Shaykh; mosquée al- (Houmt Souk; Djerba)

Sur la diffusion des formes d’architecture religieuse musulmane à travers le Sahara - Schacht, Joseph (Travaux de l'Institut de Recherches Sahariennes, 1954)
Keywords: Architecture – Djerba; Ghuraba; mosquée al- (Houmt Souk; Djerba); Jami al-Kabir; mosquée al- (Hachene; Djerba); Monuments – Djerba; Shaykh; mosquée al- (Houmt Souk; Djerba); Tîfarrûjîn; mosquée (Oualagh; Djerba)

L'artisanat traditionnel dans le département d'Alger et le territoire de Ghardaïa - Schacht, Joseph (Documents algériens, 1953)
Keywords: Artisanat – Mzab

Bibliothèques et manuscrits Abadites - Schacht, Joseph (Revue Africaine, 1956)
Schacht’s list is based on the catalogue of Makt. al-Quṭb and al-Makt. al-Ghannā’ in Beni Isguen (see p. 377 on these collections), and he did not list works already mentioned in GAL. Schacht mentions the following libraries: - Maktabat al-Quṭb in Beni Isguen, the library of the late Muḥ. b. Yūsuf Iṭfayyish. - Makt. al-Ghannā’, in the same house as the Makt. al-Quṭb. It is the library of the late Yaḥyà b. Muḥ. al-Ghanā’ī. Both these libraries are a Waqf. - The library of the late Ṣāliḥ b. ʿUmar al-Yasjanī in Beni Isguen. (In May 1972 I was told that no one is allowed entrance in this library. It is the second best library after the Makt. al-Quṭb). - The library of the late ʿAbd al-ʿAzīz al-Thamīnī in Beni Isguen. - The library of the late Saʿīd b. Yūsuf in Beni Isguen. (In May 1972 I was told that this library has been bought by Muḥ. b. Yūsuf Babānū). - The collection of Ibr. b. Bakīr. (He died in 1955 and his library has also been bought by Muḥ. b. Yūsuf Babānū). - The library of the late Yaḥyà b. Ṣāliḥ, Qāḍī of Melika, in Melika. (In May 1972 I was told that this is an important library. Its keeper was Ṣāliḥ ʿAbd al-Raḥmān). - The library of Muʿizz Aḥm. b. Yūsuf in Melika. (Member of the ʿAzzāba in May 1972). - The library of Aḥm. b. Ṣāliḥ in Melika. (Keeper in May 1972: Abū ‘l-Qāsim ʿAbd al-Ḥamīd, member of the ʿAzzāba. Called Maktabat Āl Skūtī). - The library of the late ʿUmar b. Ḥammū in El Ateuf. (In May 1972 this library was scattered). - The collection of Dāwud b. Yūsuf in El Ateuf. (In May 1972 I was given the name of Slimān b. Dāwud b. Yūsuf). - (In May 1972 I was given the name of Ayyūb b. Ibr. Jarrādī, in El Ateuf, as a possessor of Ibāḍī books). - The library of the late Bālḥājj [b. Kāsī] in Guerara. - The library of the late al-Shaykh al-Ṭarāblusī, a Waqf. (Was in the Masjid Berriane in May 1972). - The collection of ʿAbd al-Raḥmān al-Bakillī in Berriane. On page 376 note, Schacht mentions the following Ibāḍī libraries at Jerba: - The most important collection is al-Khizāna al-Bārūniyya [in al-Ḥashshān]. - Another important collection is the Khizānat al-Bāsī, in the mosque of al-Bāsī in Wālagh. This library was established in 1198/1783-4 by two brothers who traded with Istanbul, where they aquired many MSS. An old catalogue showed 225 vols., but Schacht found that all Ibāḍī works had disappeared, and that only about 100 non-Ibāḍī works remained. - The library of the Ibn Taʿrīt family has been scattered. - The larger part of the collection of the late Sul. al-Jāduwī in El-Adjim has been transferred to Hammam-Lif. - The collection of the late Ramaḍān al-Laynī was still in El-Adjim. - In Wālagh there are the Makt. al-Baʿtūr and the collection of ʿAmr b. Marzūq. - (The library of Sālim b. Yaʿqūb in Ghīzen should be added).
Keywords: Barrādī; Abū ‘l-Qāsim b. Ibrāhīm al-; Bibliothèques – Djerba; Bibliothèques – Mzab; Manuscrits – Djerba; Manuscrits – Mzab

An Unknown Type of Minbar and Its Historical Significance - Schacht, Joseph (Ars Orientalis, 1957)
Keywords: Ghuraba; mosquée al- (Houmt Souk; Djerba); Monuments – Djerba